Missed linkage to care for patients who screened positive for Hepatitis C in a tertiary care centre: Results of the Telepass project. Issue 4 (24th January 2021) - Ponziani, Francesca Romana; Santopaolo, Francesco; Siciliano, Massimo; De Belvis, Antonio Giulio; Tortora, Annalisa; Mora, Vincenzina; Fanali, Caterina; Morsella, Alisha; Balducci, Fulvio; Vetrugno, Giuseppe; D'Alfonso, Maria Elena; Cambieri, Andrea; et al.
Abstract: Italy is one of the countries on track with the WHO's agenda to eliminate hepatitis C virus (HCV) by 2030. Healthcare facilities play a crucial role in seeking patients who are infected but have not yet been treated. We assessed the effectiveness of a recall strategy, named 'Telepass' project, for patients exposed to HCV infection who have not yet been linked to care in a large tertiary care centre. The 'Telepass' project was structured in two phases: (a) a retrospective analysis first identified all anti–HCV‐positive subjects among patients who underwent pre‐operative assessment in the facility in the course of one year; (b) a following prospective phase, aimed to recall patients in need either of further diagnostic tests (ie HCV‐RNA) or treatment. A total of 12246 records of patients tested for HCV antibodies were reviewed. The overall prevalence of anti–HCV‐positive subjects was 1.83% (224/12246) with a male/female ratio of 2.07. Out of the 224 anti–HCV‐positive patients, 123 (54.91%) did not have documented HCV‐RNA tests and were therefore selected for recall. Of these, 123 were reachable and 26 (21.13%) were successfully linked to care. Ten patients (38.46%) tested HCV‐RNA positive and initiated treatment with direct‐acting antivirals (DAAs). The Telepass study highlights that a recall strategy starting from internal hospital databases can help identify patients with chronic HCV infection who have not yet been linked to care, and provides an epidemiological insight into the prevalence of HCV infection in Italy in the late DAAs era.